PREVENTING GOODS/SERVICES PROCUREMENT FRAUD IN HANDLING COVID-19 AND ITS IMPLICATION ON FINANCIAL PERFORMANCE IN SIGI DISTRICT - Sustrianti, Sustrianti; Miru, Sulaeman; Kadang, Juliana (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2022)
This research aimed to determine: 1) The influence of the internal control system on preventing goods/services procurement fraud in handling covid-19 in Sigi District, 2) The influence of compensation suitability on preventing goods/services procurement fraud in handling covid-19 in Sigi District, 3) The influence of organizational commitment to the prevention of goods/services procurement fraud in handling covid-19 in Sigi District, 4) The influence of the internal control system on the financial performance of Sigi District, 5) The influence of compensation suitability on the financial performance of Sigi District, 6) The influence of organizational commitment on the financial performance of Sigi District, 7) The influence of preventing goods/services procurement fraud in handling COVID-19 on the financial performance of Sigi District. Type of the research was quantitative approach with a sample of 30 respondents. Data analysis technique used path analysis with purposive sampling technique. The results of the research indicate that the internal control system has a positive and insignificant influence on preventing goods/services procurement fraud in handling covid-19 in Sigi District; the suitability of compensation has a positive and significant influence on preventing goods/services procurement fraud in handling covid-19 in Sigi District; organizational commitment has a positive and insignificant influence on preventing goods/services procurement fraud in handling covid-19 in Sigi District; the internal control system has a positive and significant influence on the financial performance of Sigi District; compensation suitability has a positive and significant influence on the financial performance of Sigi District; organizational commitment has a positive and significant influence on the financial performance of Sigi District and the prevention of goods/services procurement fraud in handling COVID-19 has a positive and insignificant influence on the financial performance of Sigi District. Keywords: Internal Control System, Compensation Suitability, Organizational Commitment, Fraud Prevention, Financial Performance.